Persepsi Masyarakat Tentang Merantau Di Kanagarian Sulik Aie Kecamatan X Koto Diatas Kabupaten Solok - Rahmi, Wardatur; Rianto, Slamet; Yuherman, Yuherman (STKIP PGRI Sumbar, 2013)
This study aimstoobtainandanalyzethe dataorinformationin depthperception ofthe publicaboutKanagarianwanderedSulik AieXKotodistrictAboveSolok.The research isqualitativeresearch informantswere takenwith the subjectorresponseresearchcommunitywhose family memberswanderinKanagarianSulikAieDistrictXKotoaboveSoloktotalingthirthyinformants. Datawerecollectedthroughstructuredinterviewsandobservationdocumentation. The data collectedisabout thepublic perception ofwanderthatin terms ofeducation, income, andotherlocations.These results indicatethat thefirstis based onthe public perception ofeducation,theyfeelthateducationis very importantbecausenowtheyfeelthislack ofeducationmakestheirlife difficult,sotheydecidedtomigrate. Secondly, based onthe public perception oftheir incomestatesthatthe incomethey earnis notenoughto make ends meet. Third, based onpeoples perceptionsabouttheir locationstatingthatnomadsnomadsis inKanagarianSulikAielotgenerallylocated in areasof JavaandSumatra. Fourth, based onpeoples perceptionsaboutthe otherstates thattheygo abroadisbecause ofmaritalstatus.